Realising Smart Cities in ASEAN - Gonzales, Vineles Phidel Marion (2018)
ASEAN’s rapid urbanisation has implications for important issues such as strained infrastructure, rising inequalities, and public safety and security. However, if ASEAN makes full use of technology by bringing its smart cities together, a vision of sustainable and liveable cities across the region will become achievable.